Role of casein kinase 1A1 in the biology and targeted therapy of del(5q) MDS - Schneider, Rebekka K. (2014)
The Casein kinase 1A1 gene (CSNK1A1) is a putative tumor suppressor gene located in the common deleted region for del(5q) myelodysplastic syndrome (MDS). We generated a murine model with conditional inactivation of Csnk1a1 and found that Csnk1a1 haploinsufficiency induces hematopoietic stem cell expansion and a competitive repopulation advantage whereas homozygous deletion induces hematopoietic stem cell failure. Based on this finding, we found that heterozygous inactivation of Csnk1a1 sensitizes cells to a CSNK1 inhibitor relative to cells with two intact alleles. In addition, we identified recurrent somatic mutations in CSNK1A1 on the non-deleted allele of patients with del(5q) MDS. These studies demonstrate that CSNK1A1 plays a central role in the biology of del(5q) MDS and is a promising therapeutic target.